Developing offshore natural gas hydrate from existing oil & gas platform based on a novel multilateral wells system: Depressurization combined with thermal flooding by utilizing geothermal heat from existing oil & gas wellbore. (1st November 2022) - Chen, Xuyue; Du, Xu; Yang, Jin; Gao, Deli; Zou, Yiqi; He, Qinyi
Abstract: Offshore natural gas hydrate (NGH) is universally recognized as a new alternative energy resource. If methods can be found to commercially exploit it, it is expected to significantly impact the world's energy supply. In this work, an innovative method for developing offshore NGH from existing oil & gas platform is proposed, namely depressurization combined with thermal flooding utilizing geothermal heat from existing oil & gas wellbore based on a novel multilateral wells system. Meanwhile, a numerical simulation model is developed to investigate the natural gas recovery performance of the proposed method. The study shows that the average NGH concentration of the whole NGH bearing layer is reduced by about 25% after one year production by utilizing the innovative method, and 1.6 × 10 7 m 3 natural gas is produced. Bottom hole pressure is the main controlling factor in the initial stage of NGH dissociation, while the formation temperature is the main controlling factor for the dissociation of NGH in the later stage of production, and increasing the fluid injection rate is an effective means to enhance the production performance. The study also shows that the production mode of continuous injection-intermittent production has the highest cumulative natural gas production, its production performance is proved to be the best. Highlights: A method for developing offshore NGH from existing oil & gas platform is proposed. A multilateral wells system for integrally developing NGH, oil & gas is presented. Natural gas recovery performance of the proposed method is numerically investigated. Increasing fluid injection rate is a valid means to enhance production performance. Continuous injection-intermittent production has the best production performance.